Application of foam-mat drying to produce field crab powder: Foaming process optimization, drying kinetics, and final product characterization - Nguyễn Minh Thủy; Ngo Ngoc Nhut Minh; Nguyen Bao Kha; Bùi Thị Phương Thuý; Tran Ngoc Giau; Hong Van Hao; Võ Quang Minh; Ngô Văn Tài (Journal of Agriculture and Food Research, 2025)
This study used foam-mat drying to make powder from field crab meat for the first time. In which, the effect of foaming conditions [egg albumin (EA, 7.96-16.44%) and xanthan gum (XG, 0.04-0.44%)] and drying temperature (65-80°C) on powder quality were examined. With appropriate EA and XG levels of 13.16% and 0.30%, foam density and foam expansion were 0.395 g/mL and 279.78%, respectively. The total energy required and specific energy consumption decreased. In contrast, thermal efficiency and energy efficiency rose with drying temperature, reaching 2.494–4.452%, and 1.419–1.879%, respectively. Temperature affects effective moisture diffusion coefficient according to the Arrhenius equation with an activation energy of 39.33 kJ/mol. Fitting experimental data to seven thin-layer drying models and an ANN model. The Aghbashlo model scored best, with the highest correlation coefficient. Nevertheless, the ANN model demonstrated slightly superior accuracy compared to the Aghbashlo model, indicating the potential for industrial system control. • This is the first study on production of field-crab foam-mat powder • Mathematical and ANN model was successfully to predict the drying kinetics • Quality of field-crab foam-mat powder was characterized • Field-crab foam-mat powder could be potential for industrialization
Keywords: Microencapsulation and Drying Processes; Polysaccharides Composition and Applications; Food Drying and Modeling